Fungsi dan Peranan EMKL dalam Ekspor Kelapa pada PT. Elang Sriwijaya Perkasa Palembang - Rinaldy Febrian Panggabean; Suparman Suparman; Lilis Lilis (KALAO'S MARITIME JOURNAL, 2025)
This study aims to analyze the management process of the Cargo Ship Safety Construction Certificate by PT. Putra Andalas Samudera at the Port Authority and Harbormaster Office (KSOP) Class I Dumai. This certificate is a vital document to ensure ship seaworthiness in accordance with the standards of the Directorate General of Sea Transportation. The research method used is descriptive qualitative with data collection techniques through field observations, in-depth interviews, and documentation studies during the internship period. The results indicate that the management procedure is currently conducted digitally through the Shipping and Seafarers Information System (SIMKAPEL). Although the system aims for efficiency, several main obstacles were found, namely: data entry errors by staff, excessive digital document file sizes that hinder system verification, and internet network instability causing disruptions to the central server. Optimization efforts carried out by the company include increasing the accuracy of document validation before uploading and strengthening coordination between the agent, ship owner, and KSOP authorities. This study concludes that optimal certificate management is crucial to prevent financial losses due to ship operational delays and to ensure the safety of the crew and cargo.